Efficacy of Combination Antibiotic Therapy for Refractory Pediatric Inflammatory Bowel Disease. Issue 9 (4th February 2019) - Breton, Jessica; Kastl, Arthur; Hoffmann, Natalie; Rogers, Rachel; Grossman, Andrew B; Mamula, Petar; Kelsen, Judith R; Baldassano, Robert N; Albenberg, Lindsey
Abstract: Background: Recent studies have shown that oral combination antibiotics may improve disease course in refractory inflammatory bowel disease (IBD). Here, we describe the use of combination oral antibiotics as salvage therapy in refractory ulcerative colitis (UC), Crohn's colitis, and IBD-unclassified (IBD-U) at a large pediatric IBD center. Methods: Clinical response, disease activity indices, adverse events, and clinical outcomes were measured up to 1 year after antibiotic treatment in this retrospective cohort study of children with medically refractory IBD colitis. Results: Sixty-three patients with refractory UC, Crohn's colitis, and IBD-U (median age [interquartile range IQR], 15.3 [11.2–16.5] years; median disease duration [IQR], 1.2 [0.41–4.6] years) received a combination of 3 or 4 oral antibiotics (most commonly amoxicillin, metronidazole, and either doxycycline or ciprofloxacin) for a median (IQR) of 29 (21–58) days. Thirty-four patients (54%) were deemed corticosteroid-refractory or -dependent, with the majority (62/63) having a previous or present loss of response or primary nonresponse to anti–tumor necrosis factor alpha (anti-TNFα) therapy. Use of combination antibiotics led to a significant decrease in median Pediatric Ulcerative Colitis Activity Index (PUCAI) score (IQR) from 55 (40–65) to 10 (0–40; P < 0.0001) over 3 ± 1 weeks, with 25/63 (39.7%) patients achieving clinical remission (PUCAI <10 points). The clinical benefits of oral antibiotics were independent of anti-TNFα therapy optimization. Among children entering clinical remission (n = 25), only 1 patient required surgery at 1-year follow-up, vs 10 patients in the nonresponder group. Negative predictors of response to combination antibiotics were exposure to doxycycline (odds ratio [OR], 0.25; 95% CI, 0.08–0.76) and PUCAI ≥65 at baseline (OR, 0.2; 95% CI, 0.05–0.74). Conclusions: Oral combination antibiotics appears to be an effective rescue and steroid-sparing therapy to induce remission in the short term in patients failing a biologic. Abstract : In this retrospective study, we describe the benefits of combination oral antibiotics as "salvage" therapy for refractory pediatric IBD colitis. Treatment with a combination of oral antibiotics led to clinical response in 63.5% and clinical remission in 39.7%.